Prophet Muhammad’s observations and guidance on the construction of buildings - Spahic, Omer (Da‘wah Academy, International Islamic University Islamabad, Pakistan, 2011)

(untitled)
Islamic architecture is an architecture whose functions and, to a lesser extent, form, are inspired primarily by Islam. Islamic architecture is a framework for the implementation of Islam. It facilitates, fosters and stimulates Muslims’ ‘ibadah (worship) activities, which, in turn, account for every moment of their earthly lives. Central to Islamic architecture is function with all of its dimensions: corporeal, cerebral and spiritual. The form divorced from function is inconsequential. This, however, by no means implies that the form plays no role in Islamic architecture. The form is important, but in terms of value and substance it always comes second to function and its wide scope. The identity and vocabulary of Islamic architecture evolved as a means for the fulfillment of the concerns of Muslim societies. Islamic architecture was never an end in itself. It was the container of Islamic culture and civilization reflecting the cultural identity and the level of the creative and aesthetic consciousness of Muslims. Architecture, in general, should always be in service to people. It is never to be the other way round, that is to say that architecture should evolve into a hobby or an adventure in the process imposing itself on society while forsaking, or taking lightly, people’s identities, cultures and the demands of their daily struggles. Architecture, first and foremost, should remain associated with functionality. It should not deviate from its authentic character and stray into the world of excessive invention and abstraction. In this paper, I shall discuss the observations and guidance of Prophet Muhammad (pbuh) on the construction of buildings. Indeed, Prophet Muhammad (pbuh) laid the foundation of what later came to be known as Islamic architecture by introducing the latter’s conceptual and ideological aspects which were later given their different outward appearances dictated by different contexts. The aspects contributed by the Prophet (pbuh) to Islamic architecture signify both the quintessence of Islamic architecture and the vitality that is woven through its each and every facet and feature. Thus, the permanent and most consequential side of Islamic architecture is as old as the Islamic message and the Islamic community but which at the time of the Prophet (pbuh) could take no more than an austere and unsophisticated physical form.